1996
DOI: 10.1016/s0006-3495(96)79533-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural origins of redox potentials in Fe-S proteins: electrostatic potentials of crystal structures

Abstract: Redox potentials often differ dramatically for homologous proteins that have identical redox centers. For two types of iron-sulfur proteins, the rubredoxins and the high-potential iron-sulfur proteins (HiPIPs), no structural explanations for these differences have been found. We calculated the classical electrostatic potential at the redox site using static crystal structures of four rubredoxins and four HiPIPs to identify important structural determinants of their redox potentials. The contributions from just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 28 publications
5
95
0
Order By: Relevance
“…Correlation of specific positions with the presence or absence of AlkG1-type Rds in particular alkane-degrading strains shows that the three AlkG2-type Rds from organisms that only contain AlkG2-type Rds have a valine at position 44, while all AlkG2-type Rds from organisms that also contain AlkG1-type Rds have an alanine at this position. Swartz and coworkers have found that the identity of this residue correlates with the redox potential; V44 Rds have reduction potentials that are about Ϫ50 mV while A44 Rds have values around 0 mV (38). This was substantiated by Eidsness and coworkers, who have shown that replacement of A44 by V in the P. furiosus Rd reduces the redox potential by 95 mV while the reverse replacement in the C. pasteurianum Rd results in an 86-mV increase (8).…”
mentioning
confidence: 88%
“…Correlation of specific positions with the presence or absence of AlkG1-type Rds in particular alkane-degrading strains shows that the three AlkG2-type Rds from organisms that only contain AlkG2-type Rds have a valine at position 44, while all AlkG2-type Rds from organisms that also contain AlkG1-type Rds have an alanine at this position. Swartz and coworkers have found that the identity of this residue correlates with the redox potential; V44 Rds have reduction potentials that are about Ϫ50 mV while A44 Rds have values around 0 mV (38). This was substantiated by Eidsness and coworkers, who have shown that replacement of A44 by V in the P. furiosus Rd reduces the redox potential by 95 mV while the reverse replacement in the C. pasteurianum Rd results in an 86-mV increase (8).…”
mentioning
confidence: 88%
“…However, Warshel and coworkers have shown by using the PDLD model [116,117] that the evaluation of redox potentials must take into account the protein permanent dipoles, and the penetration of water molecules. The role of the protein permanent dipoles has been most clearly established in subsequent studies of iron-sulfur proteins [118,119]. Another interesting factor is the effect of ionized groups on redox potentials.…”
Section: Redox and Electron Transport Processesmentioning
confidence: 99%
“…A pseudo-twofold axis is perpendicular to the page, passing though the Fe atom term for iron-sulfur proteins [5][6][7][8]. Quantitative estimates of the Fe III -S covalency in three Rds and in a model anion, [Fe{o-C 6 H 4 (CH 2 S) 2 } 2 ] -, have been made from the intensities of sulfur K-edge X-ray absorption spectra [9].…”
Section: 6129 Da] Frommentioning
confidence: 99%
“…Possible access of solvent water to the iron site in Rd Cp has been examined theoretically [6,7]. As part of that work, it was predicted that conversion of V44 to A in Rd Cp would shift the reversible potential by c40 mV, bringing it close to that of the protein from Desulfovibrio gigas which features A in the equivalent position.…”
Section: 6129 Da] Frommentioning
confidence: 99%